2009
DOI: 10.1007/s11325-009-0266-2
|View full text |Cite
|
Sign up to set email alerts
|

Elevated economic burden in obstructive lung disease patients with concomitant sleep apnea syndrome

Abstract: SAS may add additional economic burden on beneficiaries who already have COPD or asthma/COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 27 publications
0
48
1
1
Order By: Relevance
“…This ratio was 3.5 times in our study. In addition, in previous studies, hypertension, cor pulmonale, chronic renal failure, peptic ulcer, liver disease, and apnea were shown to increase the total cost of COPD 6,7,3335…”
Section: Discussionmentioning
confidence: 94%
“…This ratio was 3.5 times in our study. In addition, in previous studies, hypertension, cor pulmonale, chronic renal failure, peptic ulcer, liver disease, and apnea were shown to increase the total cost of COPD 6,7,3335…”
Section: Discussionmentioning
confidence: 94%
“…Our findings based on the SHHS, which is a community-based cohort study not enriched by sampling for people with lung disease, confirm that impairments in lung function that do not fall in the range associated with clinical diagnoses are nevertheless associated with a higher risk for all-cause mortality. Previous studies have shown that patients with "overlap syndrome" (COPD and SDB) have a high predisposition for adverse sequelae including COPD exacerbations and poor patient-reported outcomes (10,21). Based on such evidence, it was hypothesized that SDB and lung function (i.e., lower FEV 1 ) would synergistically augment risk for mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The nocturnal desaturations are more severe in the overlap syndrome, thus predisposing to polycythemia, pulmonary hypertension and cor pulmonale [7,10]. In addition, these patients are shown to have an elevated economic burden compared with patients with COPD alone [16].…”
Section: Discussionmentioning
confidence: 99%